Generic typifications in Amarathaceae s.str. - Iamonico, Duilio (Phytotaxa, 2018)
Centemopsis, Dasysphaera¸ Neocentema, Nototrichium, Ptilotus, and Sericostachys are the generic names in Amaranthaceae which still appear untypified. Lectotypes of these names (according to the Art. 10.1 Note 1 of ICN) are designated in the present paper. On the basis of the Art. 10.1, I also investigated here the generitypes of the names, which are not typified [Centema glomerata, Dasysphaera tomentosa, Nototrichium viride, Ptilotus corymbosus, and Sericostachys scandens]. Specimens preserved at BM, GH, and S, and an image by Lopriore were chosen for the purpose of typification. Isolectotypes for the names Nototrichium viride, and Sericostachys scandens are also indicated from among specimens deposited at BISH, K, L, P, US, and WAG. The indications as holotype/isotype by Townsend and Bean (specimens preserved at BM, K, M, and Z) for the names Centema alternifolia, Dasysphaera tomentosa, and Ptilotus corymbosus were corrected (lectotype/isolectotype) according to the Art. 9.9, ex. 10. “Ptilotus sandwicensis”, which is currently considered as the basionym of “Nototrichium sandwicense”, is a nomen nudum and therefore not validly published according to the Art. 38.1 of ICN. As a consequence, the proposed combinations “Nototrichium sandwicense” by Hillebrand, and “Psilotrichium sandwicense” by Seeman were not validly published either.